Deployable S-band Antenna for CubeSats - Lau, Elizabeth Mary Jia En (Nanyang Technological University, 2022)
CubeSats, otherwise known as Nanosatellites or Small Satellites, have been an increasing commodity in the modern world. Utilizing configurable onboard systems and hardware designs compacted to a fixed CubeSat size, these satellites are able to provide a wide range of services, from GPS tracking to the researching and monitoring of the Earth and its environment. As such, transmission of the collected data by these small satellites is crucial, especially when used for real-time services. As CubeSats are defined by their compact space and cost effectiveness, data transmission is generally transmitted through a compactable isotropic antenna. In the designs of these antennas, the conducting material folds into a small compartment in the satellite and unfurls itself from its compartment after the deployment of the satellite into open space. Although this method is sufficient in carrying transmission services, the employment of parabolic antennas has been explored in the past few years, as seen from the University of Southern California’s Aeneas satellite and NASA’s RainCube. These antennas compared to isotropic antennas provide a higher gain and narrow beamwidth, allowing for a stronger received signal strength, resulting in more reliable transmissions at faster speeds. However, to integrate these parabolic antenna designs of 1.5U, a larger volume of space is needed on the small satellite. This proposed design reduces the space needed for parabolic antennas, from 1.5U to 1U, allowing for a smaller satellite or a satellite capable of accommodating more systems and subsequently, reducing the cost of the satellite’s launch. Thus, this paper aims to explore a new design for onboard parabolic antennas, using origami methods to provide a cost efficient, low storage (1U) and high gain antenna.